2019
DOI: 10.1016/j.ibusrev.2018.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Sources of open innovation in foreign subsidiaries: An enriched typology

Abstract: This paper analyzes the drivers of multinational affiliates' innovation, using a dataset based on the Community Innovation Survey for Belgium. Specifically, we investigate the role of external knowledge sources on foreign affiliates' research efforts and innovation. We thereby develop an enriched typology by taking both the MNC and the host country perspective into consideration and distinguish between different types of subsidiaries, in order to disentangle differences in the use of knowledge sources between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 107 publications
1
22
0
6
Order By: Relevance
“…It is confirmed that research-intensive companies with FDI are exporters, which avoids their research efforts benefiting the local economy rather than the global markets. Evidence of this is that the national cooperation network is not significant, but exports are [78,86,95].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is confirmed that research-intensive companies with FDI are exporters, which avoids their research efforts benefiting the local economy rather than the global markets. Evidence of this is that the national cooperation network is not significant, but exports are [78,86,95].…”
Section: Discussionmentioning
confidence: 99%
“…Other analyses have focused on how exports influence the propensity to carry out sustainable innovation [33]. To avoid the rest of the multinational network investing immeasurable efforts in research, the subsidiaries that are most active in research export more, thus avoiding their research efforts benefiting the local economy and not the global markets [95]. Exports is a dummy variable, which takes a value of 1 if the company sells on a geographical market other than the national one, and 0 if not.…”
Section: Control Variablesmentioning
confidence: 99%
“…Thus, in addition to business networks, Andersson et al (2001 argue that external technical embeddedness facilitates subsidiaries ability to assimilate knowledge from their suppliers and customers, which enhances MNE-wide development of products and production processes. Moreover, subsidiaries' embeddedness in the local technology ecosystem, including technology ventures, universities, and research institutes, is associated with subsidiaries' ability to generate not only local but also global innovations (De Beule & Van Beveren, 2019;Isaac, Borini, Raziq, & Benito, 2019).…”
Section: Network-based Perspectivesmentioning
confidence: 99%
“…This negative relationship might appear counter‐intuitive, as it could be interpreted as evidence that top R&D performers do not pursue an asset‐seeking strategy when offshoring environmental innovation. However, to make inference on the motivation underlying offshoring strategies (asset‐exploiting vs. asset‐seeking vs. asset‐augmenting), one would need to explore other characteristics of home and host countries, including the technological specialisation of investors (Branstetter, ; De Beule & Van Beveren, ; Le Bas & Sierra, ). At a closer look, the observed unconditional negative correlation might more simply suggest that top R&D performers offshore environmental innovation activities where these are more needed, that is where the stock of environmental innovation is relatively small.…”
Section: Descriptive Evidencementioning
confidence: 99%